Avidity Studies in Anisakis simplex-Associated Allergic Diseases. (23rd May 2013) - Cuéllar, Carmen; Valls, Ana; de Frutos, Consolación; Rodero, Marta; Daschner, Alvaro
Abstract : Gastroallergic anisakiasis (GAA) and Anisakis -sensitization-associated chronic urticaria (CU+) differ with respect to specific IgE levels. We hypothesised different immunoglobulin avidities in both entities as well as their dependence on TI and fish consumption. 16 patients with GAA and 17 patients with CU+ were included, and immunoglobulin levels were analysed by CAP (Phadia). IgE and IgG avidity indexes (AvIgE and AvIgG, resp.) were also determined. IgG avidity was higher in GAA than in CU+ (P = 0.035 ), whereas there was a tendency to lower IgE avidity in GAA (P = 0.095 ). When analysing all patients, AvIgG was positively correlated with specific IgE, IgG, and IgG4 as well as total IgE (Rho between 0.66 and 0.71; P < 0.002 ), but AvIgE was negatively correlated with specific IgE (Rho −0.57; P < 0.001 ), specific IgG4 (Rho −0.38; P < 0.05 ), and total IgE (Rho 0.66; P < 0.001 ). In GAA, weekly fish consumption was positively associated with AvIgE (Rho 0.51; P = 0.05 ). A multivariate regression showed that time interval was the main explaining factor for AvIgE in GAA. We could show a differential behaviour of immunoglobulin isotype avidities in both entities and their dependence on fish-eating habits as well as on the time elapsed to the last parasitic episode.